PENGOPTIMALAN SISTEM KERJA DI PETERNAKAN AYAM DENGAN MENGGUNAKAN SENSOR AIR SEBAGAI INDIKATOR DEBIT AIR PADA TEMPAT MINUM AIR AYAM - Haruta, Adzastya; Palmaningtias, Patricia; Asmarani, Realita; Susanto, Regita (Program Kreativitas Mahasiswa - Teknologi, 2013)
In the 21st century, lots of company around the world already uses automation system to help their business. As we learn in Economic Principles, to get the maximum profit, we need to suppress the production cost. Now in Dewa-Dewi Poultry Farm, they still not adapt the automation system, use lots of worker and needs lots of cost. This problem gives us an idea to apply the automation system to reduce the worker cost, Poultry Farm can use water censor to automatically give the chicken some water, with this automation system, it will make the drink of the chicken always filled.